Double-ring type continuous rotating detonation ramjet engine - XIE QIAOFENG; WANG BING (2023)
The invention discloses a double-ring type continuous rotating detonation ramjet engine which comprises an inner cylinder, an outer cylinder and a piston, the inner cylinder is sleeved with the first outer cylinder, and an inner combustion chamber is defined by the first outer cylinder and the inner cylinder; the first outer cylinder is sleeved with the second outer cylinder, and an outer combustion chamber is defined by the second outer cylinder and the first outer cylinder; an air outlet of the air inlet channel assembly communicates with an inlet of the inner combustion chamber and an inlet of the outer combustion chamber; an air inlet of the exhaust nozzle is respectively communicated with outlets of the inner combustion chamber and the outer combustion chamber; the oil injection assembly comprises a first oil injection piece arranged on the inner cylinder and a second oil injection piece arranged on the second outer cylinder. As the inner combustion chamber and the outer combustion chamber are mutually i